Gender-related differences and attitudinal determinants towards science teaching and learning: a quantitative analysis - Gudyanga, Ephias (Exclusive Journal Publishing House, 2016)
In this study, I looked at gender related differences and attitudinal determinants towards science learning and teaching. Survey design, premised on quantitative paradigm was used. A total of 243 secondary school pupils (128 boys, 115 girls, aged 11-14 years) participated in the completion of a Likert type scale, containing, factorially grouped 65 attitude measures, following an initially piloted process. Internally reliable and unidimensional constructs for cognitive, affective and pyschomotorial elements comprised the instrument. Analysis of variance (ANOVA) was the main statistics to test the Null hypothesis (Ho). It was found out that for this sample girls have a lower liking (affective), negative beliefs (cognition) and lower action (psychomotor) orientation towards science. Conclusively, girls’ significant negative attitude towards classroom science pointed out future researchers to the etiology of such.